Internalisasi nilai harapan: Strategi integratif guru PAI dalam mengembangkan kultur sekolah berbasis karakter di Sekolah Dasar Negeri - Tjian, Melinda Khaila Nurfadilla; Supriadi, Udin; Komariah, Kokom Siti (Program Studi Magister Pendidikan Agama Islam, 2026)
Character education in elementary schools often remains mere administrative jargon due to the gap between ideal school visions and actual classroom practices. This study aims to explore the internalization strategy of the